2016
DOI: 10.1007/s00792-016-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Conserved tyrosine 182 residue in hyperthermophilic esterase EstE1 plays a critical role in stabilizing the active site

Abstract: An aromatic amino acid, Tyr or Trp, located in the esterase active site wall, is highly conserved, with hyperthermophilic esterases showing preference for Tyr and lower temperature esterases showing preference for Trp. In this study, we investigated the role of Tyr(182) in the active site wall of hyperthermophilic esterase EstE1. Mutation of Tyr to Phe or Ala had a moderate effect on EstE1 thermal stability. However, a small-to-large mutation such as Tyr to His or Trp had a devastating effect on thermal stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…Nevertheless, compared to our previous studies on EstK and EstE1, 16,19,22 we found that EstSP1 has adopted the same strategy as hyperthermophilic EstE1 rather than cold-adapted EstK, showing that cold-adapted enzymes could be specifically categorized into two sets of enzymes, i.e., psychrophilic and psychrotrophic. Furthermore, it gives insight that instead of global flexibility the localized flexibility around active site is sufficient to render psychrophilic characters, which is evident from the mutational and comparative studies of EstSP1.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Nevertheless, compared to our previous studies on EstK and EstE1, 16,19,22 we found that EstSP1 has adopted the same strategy as hyperthermophilic EstE1 rather than cold-adapted EstK, showing that cold-adapted enzymes could be specifically categorized into two sets of enzymes, i.e., psychrophilic and psychrotrophic. Furthermore, it gives insight that instead of global flexibility the localized flexibility around active site is sufficient to render psychrophilic characters, which is evident from the mutational and comparative studies of EstSP1.…”
Section: Discussioncontrasting
confidence: 68%
“…22 Additionally, the mutation of Tyr182 to a similar-sized Phe had little effect on EstE1 thermal stability, indicating that the hydrogen bond involving Tyr182 is critical for stabilization of the catalytic His loop but not for thermal stability of the enzyme, as the overall structure of EstE1 was already adapted to high temperatures. 22…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In EstE1, two residues of Val and Phe were identified to be important for its dimerization [71]. In addition, Tyr in the wall of the active site was largely responsible for the thermal stability of EstE1 [94]. In Sto-Est, Arg was shown to be critical for maintaining dimer conformation [73].…”
Section: Structures Of Bhslsmentioning
confidence: 99%
“…The low rate of amino-acid conservation at position IV hints that residue X IV could affect the enzymatic activity, given that its side chain has a suitable conformation that does not interfere with the catalytic triad, with amino acids of variable side-chain lengths occurring at position IV, including glutamine [33] and tryptophan [34]. Indeed, residue X IV is suggested to be involved in the optimal configuration of the catalytic triad [32,35] and the enzymatic activity [36][37][38], to participate in substrate binding [15,30,[38][39][40][41] and to affect the thermostability [35] of ABH fold enzymes. Site-directed mutagenesis of residue X IV in different ABH fold enzymes has confirmed its significance in the enzymatic activity, resulting in a wide range of effects upon its replacement: from decreased [32,[35][36][37] and acute loss [38] of enzymatic activity, to improved activity [36,38,41] and increased thermostability [35].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%